PENGARUH KEPEMIMPINAN DAN SIKAP KERJA PERSONIL TERHADAP KUALITAS PELAYANAN LALU LINTAS UDARA DI BANDAR UDARA SOEKARNO HATTA - Dwi Lestary; Pangsa Rizkina Aswia (Politeknik Penerbangan Indonesia Curug)
The purpose of this research is to attain how far the influence of Leadership and Personnel attitude to the performance of Air Traffic Services Quality in Soekarno Hatta Airport. Facing from the back ground problems in Soekarno Hatta Airport has identified that the performance of services (especially Air Traffic Service) not optimally yet, improving the Leadership and Personnel Attitude having an effect in direct to quality of services. Leadership individually has not significantly influence to Air Traffic Services quality at Soekarno Hatta Airport. Personnel Attitude individually has positively influence to Air Traffic Services quality at Soekarno Hatta Airport. The result of research indicate that Leadership And Personnel Attitude together have influence positively to the quality Air Traffic Services at Soekarno Hatta Airport. Coefficient Determination (R2 ) was found that equal to 88,10 % it means that various improvement of Quality of Air Traffic Service caused by various of leadership and personnel attitude, and the rest of 11,90 % may caused by other factors which is not analyzed yet in this research. In order to get more better of Air Traffic Services at Soekarno Hatta Airport. The Air Navigation Service Provider in Soekarno Hatta Airport (JATSC) shall improve the employee quality of its leadership and also improve its personnel attitude with training. Keywords : Leadership, Working Attitude, Quality, Service, Air Traffic Controller